Charcot-Marie-Tooth disease: a novel Tyr145Ser mutation in the myelin protein zero (MPZ, P0) gene causes different phenotypes in homozygous and heterozygous carriers within one family - Leal Esquivel, Alejandro (2003)
artículo -- Universidad de Costa Rica. Instituto de Investigaciones en Salud, 2003